Nanobiorremediação de pentaclorofenol e cromo hexavalente em solo residual de basalto - Ineia, Adriano (2022)
The exponential growth of the population, associated with intense unplanned industrial growth, has created serious problems in areas contaminated by toxic compounds. The improper disposal of toxic and organochlorine metallic compounds to the environment has been the subject of many studies due to their necessity and necessity, as they were impacted from areas surveyed. Given this perspective, bioremediation has become an interesting alternative and more recently a nanobioremediation. The objective of this study is to evaluate the process of this alternative in a residual basalt soil contaminated by organochlorines and toxic metals, using nano-particles of zero valiant iron (nZVI) and microorganisms from the soil. The experimental method of this study consists of determining toxicity, evaluating the effectiveness of nZVI and applying the nanobioremediation technique. Toxicity analysis will be carried out using the CO2 production method. To perform the tests, intermediate standards of 20 to 50 mg / kg of pentachlorophenol and hexavalent chromium (Cr VI) were adopted. CO2 will be measured every 02 days, in order to have a monitoring at different times of the residual contents. In order to evaluate the efficiency of degradation, it was defined the use of 04 nZVI procedures, two practices of Cr VI and PCP (50 mg/kg), these levels will happen in 04 different times (0, 24, 48, 144 days). In the premise, to evaluate a nanobioremediation, two types of contamination will be adopted, 04 nZVI adjustments (0, 10, 20 e 40 g/kg) and 06 different times (1, 8, 15, 30, 45, 60 days). Regarding the statistical decontamination of hexavalent chromium, it is noticeable to observe that the variables time and nZVI concentration are the main responsible for the response variable. Supposed justifications for this are that the time favors the reduction process and the concentration of nZVI enhances the degradation of the contaminant. For pentachlorophenol, the main variables that interfere in the response are the concentration and the type of contamination, because the nZVI interferes in the selectivity of the contaminant to be degraded, the nano particle tends to interact preferentially with the inorganic contaminant Cr VI instead of the organic PCP. It is concluded that nanobioreremediation is a technique that requires more than 60 days to be effective for the native microbiota.